2021
DOI: 10.1016/j.jtocrr.2021.100236
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Peritoneal Mesothelioma With EWSR1-ATF1 Fusion: A Case Report

Abstract: Malignant mesothelioma with EWSR1-ATF1 fusion is a rare malignancy described in young adults without asbestos exposure. To the best of our knowledge, outcomes to local and systemic therapies for this subtype of malignant mesothelioma have not been described. This case report describes the clinical course of a 19-year-old man diagnosed with malignant peritoneal mesothelioma with EWSR1-ATF1 fusion localized to the abdomen. His disease followed an aggressive course and resulted in limited survival (18 mo). There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Features of high‐grade malignancy (brisk mitotic activity and necrosis) were absent. Notably, the tumor cells in each case had patchy to negative expression of calretinin and retained nuclear expression of BAP1 16–18,22,23 . In‐frame fusion transcripts involved EWSR1 exon 7/8 and YY1 exon 2/3 16–18,22,23 .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Features of high‐grade malignancy (brisk mitotic activity and necrosis) were absent. Notably, the tumor cells in each case had patchy to negative expression of calretinin and retained nuclear expression of BAP1 16–18,22,23 . In‐frame fusion transcripts involved EWSR1 exon 7/8 and YY1 exon 2/3 16–18,22,23 .…”
Section: Discussionmentioning
confidence: 97%
“…Notably, the tumor cells in each case had patchy to negative expression of calretinin and retained nuclear expression of BAP1. [16][17][18]22,23 In-frame fusion transcripts involved EWSR1 exon 7/8 and YY1 exon 2/3. [16][17][18]22,23 Methylation studies showed clustering of EWSR1/FUS::ATF1-and EWSR1::YY1fusion-positive mesotheliomas that was similar to conventional mesotheliomas, indicating that they likely are part of the heterogeneous mesothelioma genetic spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations